Levels of engagement in participatory health systems strengthening: A systematic literature review - Jesse David Marinus; Chaïm la Roi; Christiaan Boerma (Social Sciences and Humanities Open)
Engaging participants in Health Systems Strengthening (HSS) facilitates a more person-centred approach that better addresses the complex interplay within health systems and helps to bridge the gap between knowledge and practical application. Although various participatory approaches are already used, it remains unclear how, where, and why participants are engaged within HSS. This systematic literature review investigates the extent of participant engagement, the motivations behind participatory approaches, and the specific health system building blocks that are researched. A comprehensive search identified 140 empirical studies published in English up to May 2023, selected for their focus on HSS and use of participatory approaches involving communities, patients, or citizens. Data were synthesised to assess levels of engagement, motivations, and the health system building blocks targeted.Findings reveal that, while participatory HSS studies are increasing in popularity, most studies engage participants primarily in advisory or support roles, with decision-making largely retained by academic researchers, reflecting limited levels of engagement. Common motivations for using participatory approaches include creating change and addressing power dynamics. Additionally, most studies focus on service delivery, with less attention to other critical building blocks, such as health workforce, information systems, and financing. The review further reveals that Community-Based Participatory Research (CBPR) and Participatory Action Research (PAR) are the most frequently utilised approaches; however, no substantial differences in engagement levels or motivations were found between the different approaches. But overall, there is a notable lack of documentation regarding participant engagement, which compromises scientific rigour.This review highlights the need to expand focus beyond service delivery to underrepresented health system building blocks and calls for improved documentation of engagement processes and motivations to advance the field of participatory HSS.